Voice Problems in Post-COVID-19 Patients - Susanti, Nadya; Setyaningsih, Wiwik (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Voice problems, also called dysphonia, are a common sign in people who have COVID-19. Despite this, it is often underestimated as it is a relatively less frequent and life-threatening symptom. These changes are called vocal functional changes. Most of them happen because of the immune system's response after an infection. This then causes the voice to not work as well. Objectives: This research aims to learn how often voice issues linked to COVID happen across the globe. It also checks for possible things that make these issues more likely, both when sick and later on. The purpose is to give ideas for better ways to care for people. Methods: This research design uses a systematic literature review, the selected studies are in the period 2020-2025. Research data was searched from databases, including: PubMed, Science Direct and Google Scholar. By using the search keywords (“COVID-19” OR “SARS-CoV-2”) AND (“voice impairment” OR ‘dysphonia’ OR